KERAGAMAN GENETIKA POPULASI PELAHLAR (Dipterocarpus littoralis (Bl.) Kurz) DIPULAU NUSAKAMBANGAN BERDASARKAN PROFIL ENHANCED RANDOM AMPLIFIED POLYMORPHIC DNA - Yulita, Kusumadewi Sri; Partomihardjo, Tukirin (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Dipterocarpus littoralis is a commercial timber species endemic to Nusakambangan island. Their existence is under severe threat due to habitat conversion and illegal logging. This study aimed to assess genetic diversity of this species within and among populations using E-RAPD. Three arbitrary RAPD primers were modified by addition of two nucleotides at their 5 termini.E-RAPD profiles were obtained by performing PCR amplification using the modified primers. Forty-five putative loci of E-RAPD were scored and analysed using POPGENE software. Some of the RAPD bands (OPA 9E-200 and 850 bp) were distinctively found for population 2, thus it served as population diagnostic marker for this population. Genetic diversity within population (0.1540) was higher than that of among populations (0.0418). Genetic differentiation (Gst) indicated that 21.35% of total genetic diversity in D. littoralis was attributed to the differences among populations. The highest genetic diversity was found in population 2(He:0.1923; 1:0.3158), while the lowest genetic variation was observed in population 1 (He: 0.0828; 1: 0.1209). Total genetic diversity for all population (Ht) was 0.1958 with an average value of genetic diversity within populations (Hs) was 0.1540. This fact suggested high level of genetic diversity found on these relic populations.